Daily Work Load Distribution to Increase Time Quality of Inpatients’ Medical Record Document Procurement In X Hospital - Harjanti Harjanti; Navis Yuliansyah; Kurnia Widyaningrum (Universitas Muhammadiyah Yogyakarta, 2018)
Procurement of inpatient medical record document is one of some indicators of a hospital’s minimum service standards (SPM). According to the hospital MSS, the ideal procurement of inpatient medical record document is about ≤ 15 minutes, however the procurement on the report of quality committee at the first semester on 2017 in X Hospital reaches 22,89 minutes. The study is aimed at identifying, determining the root of the problems, and trying to devise solutions to the problems. The study employs a qualitative approach by employing document analysis, in-depth interview, and ethnographic observation. The problems are identified by using three steps which are focus group discussion (FGD) by the board of directors, the head of division, and the head of unit X Hospital. The second step is time motion study at the place of inpatient registration, and the last is Urgency, seriousness, and growth (USG) in medical record unit. The study results show that the overload of inpatient admission officers’ work is known to be the root of the problem. Solution to the procurement which is not in accordance with the hospital minimum service standard is to distribute the daily workload of inpatient admission officers to related units.